Online Machine Translation and Language Learning: EFL Learners’ Practices and Beliefs - Jeane Tuilan,; Herminus Efrando Pabur,; Ignatius J. C. Tuerah, (Technium Social Sciences Journal, 2023)
With the advancement of technology, the quality of the translation generated by online machine translation (OMT) has also improved. The OMT even have become an integral part of English language learning. This present study is conducted to investigate the English as a foreign language (EFL) students’ beliefs and practices towards the use of OMT in English language learning. This qualitative study is conducted using a questionnaire as the data collection instrument. The questionnaire is administered to 22 EFL students at a university in June 2023. The data were analyzed by using frequency and descriptive analysis. The finding shows that OMTs, as believed by the students, are valuable tools in improving students’ English language learning experiences. They believe that OMTs offer many benefits for students in EFL classrooms. However, the frequent use of OMTs can lead to over-reliance, decreasing students’ confidence and self-reliance in learning English. The findings also show that students use the OMTs in EFL classrooms because of the benefits while realizing their potential drawbacks. OMTs have a significant role in EFL classrooms since they can be a valuable learning resource for students. English teachers are expected to harness the good potential of OMTs to improve the quality of English language learning.